1995
DOI: 10.1007/bf00114502
|View full text |Cite
|
Sign up to set email alerts
|

Expression of extraocular myosin heavy chain in rabbit laryngeal muscle

Abstract: The intrinsic laryngeal muscles of mammals are functionally heterogeneous, some of these muscles (e.g. the thyroarytenoid) contract extremely rapidly, like extraocular muscle, whilst others (e.g. the cricothyroid) contract as fast as limb fast muscle. The extraordinarily rapid contraction speed of extraocular muscles is associated with a fast myosin not found in limb muscles. In this work we explored the possibility that the thyroarytenoid muscle may also express this extraocular-specific fast myosin by raisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
85
0
3

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(94 citation statements)
references
References 38 publications
6
85
0
3
Order By: Relevance
“…For example, with reference to Fig. 3C, opposite conclusions could be obtained from patients 8,13,16 where MyHC I is 25-30% and from patients 18, 20 where MyHC I is 50%. There are, however, other possible explanations: i) the variability inside each muscle, carefully described for the vocalis of the dog by Bergrin et al (12), which might lead to different conclusions depending on the site of sampling, and ii) the possible consequences of the pathological conditions which might have caused a partial loss of muscle functions in the patients, all affected by laryngeal neoplasm.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…For example, with reference to Fig. 3C, opposite conclusions could be obtained from patients 8,13,16 where MyHC I is 25-30% and from patients 18, 20 where MyHC I is 50%. There are, however, other possible explanations: i) the variability inside each muscle, carefully described for the vocalis of the dog by Bergrin et al (12), which might lead to different conclusions depending on the site of sampling, and ii) the possible consequences of the pathological conditions which might have caused a partial loss of muscle functions in the patients, all affected by laryngeal neoplasm.…”
Section: Discussionmentioning
confidence: 82%
“…In rat laryngeal muscles a specific MyHC isoform (MyHC IIL) has been described by DelGaudio et al (13) and recent studies confirmed the presence of a super-fast Myosin isoform (14,15). Also in rabbit additional MyHC isoform has been identified in intrinsic laryngeal muscles, migrating as fast MyHC-EO isoform detected in extraocular muscles (16). In laryngeal muscles of the dog a fourth MyHC isoform has been described and identified with MyHC IIB (12,17,18).…”
Section: Discussionmentioning
confidence: 86%
“…The anti-EO MAb 4A6 was shown to be EO MyHC specific in rabbits (Lucas et al 1995), humans (Pedrosa-Domellof et al 2000), rats (Rubinstein and Hoh 2000), and cats (Lucas CA and Hoh JFY, unpublished data). Anti-2B MyHC MAb 10F5 has been shown to be specific for this isoform in the mouse (Nair-Shalliker et al 2004), rat, rabbit, cat, baboon , and even marsupial species (Zhong et al 2008), using both immunohistochemistry and Western blots.…”
Section: Isoforms Of Myhc Expressed In Equine Laryngeal Musclesmentioning
confidence: 97%
“…However, laryngeal muscles show phylogenetic plasticity. In small animals like the rat and rabbit, they may express the two fastest MyHCs, EO and 2B (Lucas et al 1995;Rhee et al 2004). EO MyHC expression is lost in the cat (Rhee and Hoh 2008) and dog (Wu et al 2000b;Toniolo et al 2007), whereas neither of these MyHCs is found in laryngeal muscles of large animals such as human (Li et al 2004), baboon (Rhee and Hoh 2008), and cattle (Toniolo et al 2005).…”
mentioning
confidence: 99%
“…The fact that 10F5 is highly specific for mammalian 2B MyHC is indicated by Western blots in many eutherian and marsupial species (Zhong et al 2001(Zhong et al ,2008. MAb 4A6 has been shown to be broadly EO MyHC specific in mammals, including rabbits (Lucas et al 1995), rats (Rubinstein and Hoh 2000;Rhee et al 2004), cats (C.A. Lucas and J.F.Y.…”
Section: Ihcmentioning
confidence: 99%